The Effect of Resilience and Social Support on Nurses' Job Satisfaction with Mediation Variables of Sleep Quality and Mental Support at Yarsi Hospital, Central Jakarta - Istiara Henoviota; Corry Yohana; Widya Parimita (Return : Study of Management, Economic and Bussines, 2026)
Nurses’ job satisfaction is a crucial factor influencing healthcare service quality, employee retention, and organizational performance. However, nurses frequently experience high workloads, shift-related pressures, emotional demands, and occupational stress, which may reduce their professional satisfaction. This study aimed to examine the effects of resilience and social support on nurses’ job satisfaction by analyzing the mediating roles of sleep quality and mental support at YARSI Hospital, Central Jakarta. This research employed a quantitative approach with a cross-sectional design. Data were collected through structured questionnaires distributed to 160 nurses selected using a purposive sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to evaluate the direct and indirect relationships among the variables. The results showed that resilience and social support had significant positive effects on job satisfaction, sleep quality, and mental support. Mental support significantly mediated the relationships between resilience and social support and job satisfaction, whereas sleep quality did not significantly mediate these relationships. The findings indicate that psychological and social mechanisms played a more dominant role than physiological recovery factors in determining nurses’ job satisfaction. This study concludes that strengthening resilience, social support systems, and workplace mental support programs is essential for improving nurses’ occupational well-being and job satisfaction. The findings provide practical implications for hospital management in developing effective human resource strategies to enhance nurses’ psychological well-being and workplace satisfaction.